1974
DOI: 10.1104/pp.53.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Maize Mitochondria: Purification and Characterization of Ribosomes and Ribosomal Ribonucleic Acid

Abstract: Mitochondria were prepared from etiolated maize shoots (Zea nuays L. var. McNair 508) by homogenization followed by differential centrifugation and equilibrium banding in discontinuous sucrose or Renografin-sucrose gradients. Mitochondria prepared by sucrose banding showed better physiological integrity than those prepared by Renografin-sucrose banding, although both procedures yielded mitochondria that showed respiratory control and coupling of oxidation to phosphorylation of ADP. Mitochondria prepared by Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…However, given that the 70S and 80S ribosomes of C. reinhardtii sedimented closely on sucrose gradients (Yamaguchi et al, 2003) and that mitochondrial ribosomes from higher plants have been observed to sediment anywhere between 70S (Vasconcelos and Bogorad, 1971; Pinel et al, 1986) and 78S (Leaver and Harmey, 1973, 1976; Pring, 1974), the above observations highlight the importance of early fractionation steps, orthogonal to sucrose gradient purification, in obtaining pure cytosolic ribosomes required for confident discrimination of cytosolic and organellar ribosomal proteomes. In this author’s view, this technical point is worth highlighting given the potential functional and evolutionary significance of parallel-targeting of r-proteins to multiple ribosomes in eukaryotic cells and the fact that just a few simple protocol modifications could greatly enhance the utility of future studies in addressing this important possibility.…”
Section: Type II S15a Proteins: Components or Contaminants Of The Aramentioning
confidence: 99%
“…However, given that the 70S and 80S ribosomes of C. reinhardtii sedimented closely on sucrose gradients (Yamaguchi et al, 2003) and that mitochondrial ribosomes from higher plants have been observed to sediment anywhere between 70S (Vasconcelos and Bogorad, 1971; Pinel et al, 1986) and 78S (Leaver and Harmey, 1973, 1976; Pring, 1974), the above observations highlight the importance of early fractionation steps, orthogonal to sucrose gradient purification, in obtaining pure cytosolic ribosomes required for confident discrimination of cytosolic and organellar ribosomal proteomes. In this author’s view, this technical point is worth highlighting given the potential functional and evolutionary significance of parallel-targeting of r-proteins to multiple ribosomes in eukaryotic cells and the fact that just a few simple protocol modifications could greatly enhance the utility of future studies in addressing this important possibility.…”
Section: Type II S15a Proteins: Components or Contaminants Of The Aramentioning
confidence: 99%
“…Plant mitoribosomes also contain a 5 S RNA component [5] but not, apparently, the '5.8'S RNA species which is hydrogen-bonded to the large (26 S) rRNA of plant cytoribosomes [6]. The sedimentation coefficient of higher-plant mitoribosomes is 77-78 S [2,3] , very similar to that of plant cytoribosomes (80 S), Nevertheless, protein synthesis in plant mitochondria is sensitive to many of the antibiotics which differentially inhibit protein synthesis in prokaryotes, as well as in chloroplasts and in mitochondria of other organisms…”
Section: Introductionmentioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. 3841 distinct protein synthesizing system (14,15) which makes a limited range of polypeptides (16,17), similar in both number and molecular-weight range to those synthesized by mitochondria from Ascomycetes and animal cells (18). In plants these polypeptides remain to be identified, but it is likely, by analogy with other cell types, that many of them are components of enzyme complexes located in the inner mitochondrial membrane (18).…”
mentioning
confidence: 99%